"Smart Puzzle" Game Helping Children Learn to Read - Septyana Hardianti Yunanto; T. Brenda Chandrawati (SISFORMA, 2016)
The game is one of the media for learning. One of the games that can be used as media of instruction is "Smart Puzzle" games. "Smart Puzzle" games are educational games are used as tools to teach reading to kindergarten with a game concept devised letters tailored to a different picture in each parts. This game is distinguished into three categories, namely category animals which consists of 10 stage and 2 mini games, a profession category consists of 10 stage and 2 mini games and family categories that consists of 6 stage and 1 mini games. "Smart Puzzle" game has 4 components of games as a medium of instruction. 4 the game components, including drafting letters, complete the picture, match the job with their workplace and learning family tree. With the 4 components of this being the excess of the game "Smart Puzzle" compared to other reading games.